Automated Power Factor Correction for Smart Home - Alhasnawi, Bilal Naji; H.Jasim, Basil (Iraqi Journal for Electrical and Electronic Engineering, 2018)
In the current scenario, power factor has become an important concern in all industries. Poor power factor gives rise to many problems which result in financial loss of industries and also for the commercial users. The main concern of this work is to improve the usage of real power with respect to reactive power hence improving the power factor. Here we have used the technique of relay switching method with a capacitor so that any drop in power factor can be sensed by the controller and switch the capacitor as required. This will not only help to improve power factor but also demand of electricity supply on utility side will be reduced. The Significance of this work is to build an APFC (Automatic Power Factor Correction) Unit. The APFC appliance calculates the reactive power (KVAR) expended by a system’s load and compensates the lagging PF (power factor) utilizing capacitances from capacitor banks.